Enclosed Experimental Ecosystems and Scale Tools for Understanding and Managing Coastal Ecosystems - Petersen, John E.; Kennedy, Victor S.; Dennison, William C.; Kemp, W. Michael (Springer New York : Imprint: Springer, 2009)
The environmental challenges now facing humanity, ranging from climate change to urbanization to invasive species to agricultural and industrial pollutants are particularly acute in the coastal zone. Research in this region and in other aquatic ecosystems is complicated by interactions that occur over broad scales of time, space, and ecological complexity. Enclosed experimental ecosystems (mesocosms and microcosms) have become critical research tools because they provide a degree of control not achievable through field experiments. Yet to date, techniques for systematically extrapolating results from small-scale experimental ecosystems to larger, more open, more biodiverse, and more heterogeneous ecosystems in nature have not been well developed. This book is designed to provide scientists, resource managers and students with a comprehensive and practical guide and reference for improving the design and interpretation of research conducted in experimental ecosystems.